Ozalism: Successes and Contradictions of Turkish Neoliberalism - Valer’evna Pronina, Veronika (2021)
The article presents the main signs of political, economic and social reforms in the era of Turgut Ozal - a head of economic activity, the Prime Minister and the President of the Republic of Turkey during the 1980s and 1990s. Political ozalism (domestic and foreign policy), economic ozalism, social ozalism. Turgut Ozal 's ideology is a synthesis of technological Westernization and cultural Turkism and Islamism. Many Turkish scholars call his ideology "Turkish-Islamic synthesis" (Atila Eralp et al., 1993). Following the principles of the new ideology, Turkey has embarked on the path of achieving a special position in the international arena that would allow it to participate in global processes. it should be emphasized that Ottoman and Islamic culture was one part of the political course of Ozalism. The second half was economic and political liberalism. Such ambivalence or dualism of views is linked to Turgut Ozal’s belief that modernization can only be carried out through liberalization. The Prime Minister of the Republic used economic liberalism to achieve political pluralism. The article outlines the peculiarities of the "Turkish miracle," which occurred as a result of the measures taken to thoroughly revise domestic economic regulation and state intervention in the economy. The essence of them was a significant reorganization, weakening the legal and de facto monopoly of the state over the economy of the country.